Enhancing the Adhesion of CuO Nanoparticles for Antibacterial Activity by Using Ecofriendly Surface Modification of Cotton Fabric - G. Shanmugavelayutham; S. B. Tharchanaa; T. Anupriyanka (Current Innovations in Chemical and Materials Sciences Vol. 3, 2023)
The present chapter employs a facile and environmentally cleaner plasma technology to induce adhesion between the cotton fabric and CuO nanoparticles. The oxygen plasma pre-treatment of cotton fabric was performed using DC glow discharge plasma for different plasma treatment times (5, 10 and 15 min) with constant pressure and power. The untreated and plasma treated cotton fabrics were analysed by contact angle, Atomic Force Microscopy (AFM),X-ray Photoelectron Spectroscopy (XPS), X-ray Diffraction (XRD), Filed Emission Scanning Electron Microscopy (FESEM) and elemental mapping analysis. The untreated cotton exhibits a flatter surface with an average surface roughness of 24 nm, whereas the roughness of plasma treated cotton fabric increases gradually with an increase in plasma treatment time. The AFM results show that when the plasma treatment time increases, the treated fabric’s surface roughness increases as well. Cotton fabric’s stickiness is caused by oxygen-rich functional groups that are introduced to the surface by the oxygen plasma treatment, according to XPS study. The 15 min oxygen plasma treated cotton fabric is optimised to coat the CuO nanoparticles based on the AFM and XPS analyses. Additionally, gram-positive and gram-negative bacteria were shown to exhibit considerable antibacterial activity when the CuO nanoparticles covered plasma treated cotton fabric was subjected to an antibacterial test. It is concluded that the adoption of plasma technology is a possible alternative for imparting hydrophilic properties to textiles in a cleaner and environmentally friendly manner with- out any hazardous chemicals as pursued by traditional chemical processes. GRAPHICAL ABSTRACT